The third molar as an age marker in adolescents: new approach to age evaluation - Rozkovcova, Eva; Dostalova, Tatjana; Markova, Marie; Broukal, Zdenek (Journal of forensic sciences, 2012)
Adolescence is a relatively short period between childhood and adulthood. It is very difficult to determine adulthood based on biological indicators. The third molar may be considered a potential age marker for the period between the ages of 16-21. Our study evaluated a set of 1700 panoramic radiographs of individuals aged between 5 and 21 years. Results confirmed the statistically significant difference in the course of third molars development. The mean deviation for individuals with one third molar agenesis is -0.98 years, for individuals with two third molars agenesis -1.89 years, and with three molars agenesis -3.28 years. Thus, the extent of the deviation is directly proportional to the number of unformed third molars. The calculation of age according to the mean of stages of all third molars could lead to the underestimation of age. No intergender differences were found. Age determination using third molars could be used for forensic purposes.
Keywords: molár třetí; dospělí; Female; dítě; předškolní dítě; Adult; mladý dospělý; ženské pohlaví; Forensic Dentistry; rentgendiagnostika panoramatická; Adolescent; lidé; Molar, Third; Sex Characteristics; Age Determination by Teeth; určení zubního věku; Male; Czech Republic; Child, Preschool; pohlavní dimorfismus; Young Adult; Radiography, Panoramic; soudní stomatologie; Česká republika; Child; mužské pohlaví; mladiství; Humans